Analisis Faktor yang Mempengaruhi Kinerja Pegawai: Studi Kasus Bank XYZ - Novia Naingolan; Syamsul Maarif; Anggraini Sukmawati (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
The purpose of this study was to analyze the effect of competency, training, and leadership style on the performance of employee of PT Bank XYZ in Wilayah Medan. The research population is all employees of PT Bank XYZ in the Medan Region. Total number of data surveyed were 75 employees. The Questionnaires were distributed with purposive sampling techniques method. The data obtained processed by using SEM-PLS to determine the effect of the variables tested. The results of the study indicate that training has a significant influence on competencies but does not have a direct influence on employee performance. Leadership has a significant influence on competencies and has a significant influence on employee performance. Competence has a significant influence on employee performance. The results of determining the Performance Improvement Strategy using the Analytical Hiercy Process obtained that the company needs to improve the criteria for quality improvement and the company compatible reward system.